2014
DOI: 10.1016/j.mrgentox.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the aneugenic and polyploidy-inducing effects of fisetin and two model Aurora kinase inhibitors

Abstract: Fisetin, a plant flavonol commonly found in fruits, nuts and vegetables, is frequently added to nutritional supplements due to its reported cardioprotective, anti-carcinogenic and antioxidant properties. Earlier reports from our laboratory and others have indicated that fisetin has both aneugenic and clastogenic properties in cultured cells. More recently, fisetin has also been reported to target Aurora B kinase, a Ser/Thr kinase involved in ensuring proper microtubule attachment at the spindle assembly checkp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
(35 reference statements)
0
12
0
1
Order By: Relevance
“…The statistical model produced high aneugen probability scores that abruptly switched to high clastogen scores, the latter only occurring at concentrations that exceeded our cytotoxicity limit. It is not clear whether these were spurious results associated with overt toxicity, or whether they were related to observations made by Eastmond and colleagues who reported that fisetin is aneugenic at low concentrations, with clastogenic activity evident at higher concentrations [Olaharski et al, ; Gollapudi et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…The statistical model produced high aneugen probability scores that abruptly switched to high clastogen scores, the latter only occurring at concentrations that exceeded our cytotoxicity limit. It is not clear whether these were spurious results associated with overt toxicity, or whether they were related to observations made by Eastmond and colleagues who reported that fisetin is aneugenic at low concentrations, with clastogenic activity evident at higher concentrations [Olaharski et al, ; Gollapudi et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…As a mechanism for these mitotic errors, Aurora B kinase was identified as a direct target of fisetin since Aurora B activity was significantly reduced by fisetin treatment [52]. Effects of fisetin on chromosome damage were investigated by Gollapudi et al [53] and compared with two known Aurora kinase inhibitors, VX-680 and ZM-447439. Fisetin treatment of human lymphoblastoid TK6 cells resulted in induction of aneuploidy and polyploidy as indicated by increase in kinetochore-positive micronuclei, hyperdiploidy, and polyploidy.…”
Section: Anti-cancer Activity Of Fisetinmentioning
confidence: 99%
“…Fisetin treatment of human lymphoblastoid TK6 cells resulted in induction of aneuploidy and polyploidy as indicated by increase in kinetochore-positive micronuclei, hyperdiploidy, and polyploidy. These observations suggested that fisetin could induce multiple types of chromosomal abnormalities in human cells and warranted caution in the use of fisetin containing products [53]. …”
Section: Anti-cancer Activity Of Fisetinmentioning
confidence: 99%
“…Another reason for this observation could be the timing to monitor polyploidy. Thus, in a previous study using a recovery time of 12 hr after 24 hr continuous treatment, an optimal polyploidy response by the aneugenic compound fisetin was reported [Gollapudi et al, ].…”
Section: Discussionmentioning
confidence: 99%